2017
DOI: 10.1590/1980-5373-mr-2016-0628
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sn Doped ZnS Thin Films Synthesized by CBD

Abstract: Zinc sulphide (ZnS) thin film were prepared using chemical bath deposition (CBD) process and tin (Sn) doping was successfully carried out in ZnS. Structural, morphological and microstructural characterization was carried out using XRD, TEM, FESEM and EDX. XRD and SAED pattern confirms presence of hexagonal phase. Reitveld analysis using MAUD software was used for particle size estimation. A constantly decreasing trend in particle size was observed with increasing tin incorporation in ZnS film which was due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…However, the intensity of the peaks was found to be gradually decreasing with an increase in deposition temperature, which indicates a progressive transformation of the CZS oriented polycrystalline phase to a distinct ZnS phase. This shows a separation from the deposited CZS thin films to ZnS with increasing deposition temperature [16][17][18][19][20]. Increasing the deposition temperature from 400 to 430 ᴼC reveals that the deposited material suddenly changes to polycrystalline ZnO (JCPDS 36-1451) with different peaks orientation.…”
Section: Structural Analysismentioning
confidence: 99%
“…However, the intensity of the peaks was found to be gradually decreasing with an increase in deposition temperature, which indicates a progressive transformation of the CZS oriented polycrystalline phase to a distinct ZnS phase. This shows a separation from the deposited CZS thin films to ZnS with increasing deposition temperature [16][17][18][19][20]. Increasing the deposition temperature from 400 to 430 ᴼC reveals that the deposited material suddenly changes to polycrystalline ZnO (JCPDS 36-1451) with different peaks orientation.…”
Section: Structural Analysismentioning
confidence: 99%
“…The structural and luminescent properties of ZnS can be tuned by TM dopants such as Ni, Fe, Mn, Cu, and so forth. [38] Although there are extensive experimental [39–42] and theoretical [43–48] studies have been found, but to the best of our knowledge, the experimental and theoretical investigation of doped systems especially those doped with 3d elements is found less.…”
Section: Introductionmentioning
confidence: 99%
“…Zinc sulfide (ZnS) is one of the direct II-VI semiconductor compounds with large band gap energy of ∼ 3.65 eV at room temperature exhibits a wide optical transparency from the ultraviolet to the infrared region [1]. The material crystallizes in both cubic and hexagonal forms and it is used a material of reference to test several theoretical models in condensed material physics [2].…”
Section: Introductionmentioning
confidence: 99%
“…Thus they have become more popular in recent times. ZnS thin film has been grown by using electrodepositon and various chemical techniques [10] such as Sol-gel [1], Spin coating [5], Spray Pyrolysis [11], chemical vapor deposition and chemical bath deposition [12] etc. The technique of electrodepositon is simple, inexpensive and can be adaptable to large area processing with low fabrication cost.…”
Section: Introductionmentioning
confidence: 99%